PENGARUH KUALITAS LAYANAN, EXPERIENTIAL MARKETING, WORD OF MOUTH DAN CITRA PERUSAHAAN TERHADAP KEPUASAN PELANGGAN (Studi Kasus Pada Brastagi Supermarket Rantauprapat) - Dewi Sri Purwati; Zufrie Zufrie (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2021)
In the last few decades, customer satisfaction is an absolute must for service or goods provider companies. Various concessions were developed in order to achieve this goal. Improving service quality is one of the strategies that must be developed. Service quality is a strategy that must have its own characteristics in a company to be able to win the competition. Experiential marketing, word of mouth and building a positive image of a company are some of the strategies that can be used to increase customer satisfaction. Therefore, this study aims to identify and analyze the effect of Service Quality, Experiential Marketing, Word Of Mouth and Corporate Image on Customer Satisfaction. The population in this research are customers at the Brastagi Supermarket Rantauprapat with the sample determined using the Wibisono formula, which is fulfilled to be 100 people. Collecting data using research questionnaires which were distributed directly by researchers in order to obtain research primary data. The analysis technique used in processing the data used multiple regression test to answer the research hypothesis. The results showed that partially service quality had a positive and significant effect on customer satisfaction with a calculated t1 value of 2.388 > ttable of 1.660 with a significance of 0.019 <0.005. Experiential Marketing has a positive and significant effect on customer satisfaction with a calculated t2 value of 2.127 > ttable of 1.660 with a significance of 0.036 <0.005. Word of Mouth has a positive and significant effect on customer satisfaction with a calculated t3 value of 3.641 > ttable of 1.660 with a significance of 0.000 <0.005. Company image has a positive and significant effect on customer satisfaction with a calculated t4 value of 4.144 > ttable of 1.660 with a significance of 0.000 <0.005. Simultaneously service quality, Experiential Marketing, Word Of Mouth and company image have a positive and significant influence on customer satisfaction with an Fcount of 96.572 < from Ftable 3.09 with a significance level of 0.000 > 0.05 at a 95% confidence level and 5% Alpha.